Prognostic Impact of Peak Aortic Jet Velocity in Conservatively Managed Patients With Severe Aortic Stenosis: An Observation From the CURRENT AS Registry. Issue 7 (24th July 2017) - Nakatsuma, Kenji; Taniguchi, Tomohiko; Morimoto, Takeshi; Shiomi, Hiroki; Ando, Kenji; Kanamori, Norio; Murata, Koichiro; Kitai, Takeshi; Kawase, Yuichi; Izumi, Chisato; Miyake, Makoto; Mitsuoka, Hirokazu; et al.
Abstract : Background: There are limited data regarding the risk stratification based on peak aortic jet velocity (Vmax) in patients with severe aortic stenosis (AS). Methods and Results: Among 3815 consecutive patients with severe AS enrolled in the CURRENT AS (Contemporary Outcomes After Surgery and Medical Treatment in Patients With Severe Aortic Stenosis) registry, the study population consisted of 1075 conservatively managed patients with Vmax ≥4.0 m/s and left ventricular ejection fraction ≥50%. The study patients were subdivided into 3 groups based on Vmax (group 1, 4.0 ≤ Vmax <4.5 m/s, N=550; group 2, 4.5 ≤ Vmax <5 m/s, N=279; and group 3, Vmax ≥5 m/s, N=246). Cumulative 5‐year incidence of AS‐related events (aortic valve–related death or heart failure hospitalization) was incrementally higher with increasing Vmax (entire population; 38.0%, 49.4%, and 62.8%, P <0.001; symptomatic patients; 55.7%, 60.9%, and 72.2%, P =0.008; and asymptomatic patients; 29.4%, 38.9%, and 47.7%, P =0.005). After adjusting for confounders, the excess risk of group 2 and group 3 relative to group 1 for AS‐related events remained significant (hazard ratio, 1.39; 95% CI, 1.07–1.81; P =0.02, and hazard ratio, 1.53; 95% CI, 1.17–2.00; P =0.002, respectively). The effect size of group 3 relative to group 1 for AS‐related events in asymptomatic patients (N=479) was similar to that in symptomatic patients (N=596; hazard ratio, 1.59; 95% CI, 1.01–2.52; P =0.047, and hazard ratio, 1.67; 95% CI, 1.16–2.40, P =0.008, respectively), and there was no significant overall interaction between the symptomatic status and the effect of the Vmax categories on AS‐related events (interaction, P =0.88). Conclusions: In conservatively managed severe AS patients with preserved left ventricular ejection fraction, increasing Vmax was associated with incrementally higher risk for AS‐related events. However, the cumulative 5‐year incidence of the AS‐related events remained very high even in asymptomatic patients with less greater Vmax.